Diversity of birds in the coastal zone of the Bahía Ballena and Puerto Cortés, Costa Rica (UNED Research Journal, 2019)
Introduction: birds are important components of biodiversity and play a fundamental ecological role in dispersion and pollination, as well as characterizing the conservation status of ecosystems. Objective: to determine the abundance and diversity of birds in the coastal area of Bahía Ballena and Puerto Cortés districts in the southern zone of Osa. Methods: to preliminarily characterize forest stand avifauna in two Costa Rican sites from June 2017 to April 2018, I counted birds in 30-50 m transects along the Morete, Ballena, Tortuga and Coronado rivers. Results: I recorded 158 individuals of 35 species and 19 families. Ramphocelus passerinii dominated, with 30 sightings. Morete river and the Ballena creek shared 40% species (only 25% for Morete-Coronado). The H' Shannon-Wiener diversity was moderate: Tortuga 2,43; Morete 2,35; Coronado=2,27 and Ballena 2,22. Conclusion: these riparian forest protection zones are used by most species at some point of their life and are fundamental in their required ecological matrix.
Keywords: nirds; diversity; Ballena Bay; Puerto Cortes; Costa Rica